Anthropometry of newborns from Białystok city - Bogusłowicz, Wanda; Gładykowska-Rzeczycka, Judyta (Anthropological Review, 1979)
The aim of this paper is to conclude upon secular change of newborns from Białystok city over a period of 10 years. To this end a set of morphological traits of newborns born in 1966 has been compared with a respective data on subjects born in 1976. The set of characters comprised: body weight, body length, head circumference and chest circumference. Attention has been paid to differences resulting from parity and. sexual dimorphism. From among 2,000 examined subjects Tór the analysis were chosen 1,786 for some individuals had been excluded as deviating from a norm (diseases of mothers, multiple births etc.). Statistical methods have been employed for elaboration of metric data. The main results „are as follows: 1. The highest value of body weight is characteristic for male newborns born from the fourth pregnancy and female newborns being a result of the third pregnancy (Table 3). 2. Newborns of diverse parity show differences in several morphological traits in both 1966 and 1976 samples (Table 4). 3. Sexual dimorphic differences are greater in 1966 sample than in the 1976 one. This suggests a trend toward disapperance of differences between male and female newborns (Table 5). 4. Comparisons between Bialystok data and other Polish samples do not reveal significant regional differences in newborn morphology. More detailed interpretation. of results could be obtained after completion of further studies being now under way and including socio-economic examination of Families together with monpho-physiological studies of mothers and offspring.